Excitability of spinal neural function during motor imagery in Parkinson’s disease - Suzuki, Toshiaki (Funct Neurol, 2014)
We analyzed thenar muscle F-waves after stimulating the median nerve at the wrist in subjects during two motor imagery conditions: holding and not holding the sensor of a pinch meter between the thumb and index finger. Our aim was to determine whether mental simulation without the muscle contraction associated with motion can increase the excitability of spinal neural function in patients with Parkinson’s disease (PD). F-waves of the left thenar muscles were examined in 10 patients with PD under resting, holding and motor imagery conditions. For the holding condition, the subjects held the sensor of the pinch meter between their thumb and index finger. For the motor imagery conditions, the subjects were asked to imagine a 50% maximal voluntary isometric contraction holding and not holding the sensor of the pinch meter between their thumb and index finger (motor imagery “with”/“without sensor”). Persistence during motor imagery under the “with sensor” condition increased significantly compared with persistence during resting (n=10, z=2.2509, p=0.0244, Wilcoxon test). The F/M amplitude ratio during motor imagery under the “with sensor” condition increased significantly compared with that during resting (n=10, z=2.1915, p=0.0284, Wilcoxon test). Motor imagery under the “with the sensor” condition increased excitability of the spinal neural output to the thenar muscles. Because excitability of the spinal neural output to the thenar muscles during motor imagery “with the sensor” was significantly higher than that during resting, we suggest that movement preparation for a motor imagery task is important in patients with PD.